Mentoring of Master Teachers in Higher-Order Thinking Skills Training for Junior High School Science Teachers in Bogor Regency - Murni Murni (LPPM Universitas Yudharta Pasuruan, 2022)
The purpose of this community service activity is to carry out activities to disseminate science subject for higher-order thinking skills by master teachers to Junior High School teachers and to improve the concept abilities of Junior High School teachers in Bogor Regency regarding science subject for higher-order thinking skills. The activity was carried out at SMP Negeri 1 Dramaga involving 23 science teachers and at SMP Negeri 2 Cibinong involving 25 science teachers. This activities used participatory approach. The steps for implementing this disseminate activity are: the preparation, mentoring of the master teacher, training implementation, and analyzing pretest and posttest data. The results of N-Gain, it was obtained that there was an increase in higher-level thinking skills by 0.75 with a high category for teacher participants at SMP Negeri 1 Dramaga, and by 0.62 with a moderate category for teacher participants at SMP Negeri 2 Cibinong.